Indices of Bad Governance by African Political Leaders: The Case Study of Central African Republic, Democratic Republic of the Congo and Uganda - Blaise Ngambinzoni Kombeto; Romain Bakola Dzango; Modeste Ndaba Modeawi; Gédéon Bongo Ngiala; Muhammad Ridwan; Koto-te-Nyiwa Ngbolua (Budapest International Research and Critics University, 2021)
Marcel SONY LabouTansi, the author of the novel